Use of Multi-Criteria Decision Method (MCDM) in determining the best suitable location for solar energy production in Chamchamal district - Amin, Dr.Hemn Nasruddin Mohammed Amin (Sulaimani Journal for Humanities, 2025)
This research focuses on identifying the most suitable locations for solar energy production. It is a practical climatological study that employs advanced geographic programs, techniques, and models, and has been implemented in Chamchamal District. Chamchamal District is located in the semi-mountainous region of eastern Kurdistan Region, administratively belonging to Sulaymaniyah Governorate, with a total area of 3439.78 km². Through the application of a multi-criteria decision-making approach, the study examines both the natural and human factors influencing the selection of optimal sites for solar energy projects, aiming to utilize solar power as an alternative to conventional energy sources for electricity generation. Solar energy is a sustainable source with minimal depletion, is clean, and environmentally friendly. The study concludes that, according to the results of the Analytic Hierarchy Process (AHP) model, the “entirely unsuitable” category occupies the smallest area (1.31%), while the “moderately suitable” category covers the largest area (59.98%). The “low suitability” category accounts for 6.78%, whereas the “suitable” and “highly suitable” categories represent 28.72% and 3.22%, respectively. The suitable zones are predominantly located near power transmission lines, and the highly suitable areas are also close to these lines as well as densely populated settlements—particularly Chamchamal city and the centers of Shorish and Takya subdistricts. It is recommended that solar energy projects be established within the highly suitable and suitable zones.
Keywords: Best location; solar energy; Chamchamal district; model (AHP)